Building Keyword-Indexed Virtual Libraries in a Logic Programming Environment - Lima, Edirlei Soares de; Barbosa, Simone Diniz Junqueira; Feijó, Brunoó; Furtado, Antonio Luz (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
KW-GPS is a system to assist users intent on enjoying Web resources related to a domain-restricted collection of stories. In this system, each story is referenced in a virtual library in terms of the following data: (1) the URLs of resources associated with the story, which include but are not limited to plot-summaries, narrative texts, and videos; and (2) keywords of different classes, which serve as a multi-aspect index mechanism. Library items also include story templates, representing narrative motifs. Furthermore, a reduced version of the tool runs the basic rank-and-show process on mobile devices.